Evaluation of preventive, supportive and awareness building measures among international students in China in response to COVID-19: a structural equation modeling approach - Tanwne Sarker; Apurbo Sarkar; Md. Ghulam Rabbany; Milon Barmon; Rana Roy; Md. Ashfikur Rahman; Kh. Zulfikar Hossain; Fazlul Hoque; Muhammad Asaduzzaman (BMC, 2021)
Abstract Background Education institutions promptly implemented a set of steps to prevent the spread of COVID-19 among international Chinese students, such as restrictive physical exercise, mask wear, daily health reporting, etc. Success of such behavioral change campaigns largely depends on awareness building, satisfaction and trust on the authorities. The purpose of this current study is to assess the preventive, supportive and awareness-building steps taken during the COVID-19 pandemic for international students in China, that will be useful for planning such a behavioral change campaign in the potential pandemic situation in other parts of the world. Methods We conducted an online-based e-questionnaire survey among 467 international students in China through WeChat. The data collection duration was from February 20, 2020 to March 10, 2020 and we focused on their level of awareness, satisfaction, and trust in authorities regarding pandemic measures. Simple bivariate statistics was used to describe the background characteristics of the respondents along with adoption of the partial least squares-structural equation modeling (PLS-SEM) as the final model to demonstrate the relationship between the variables. Results In our study, the leading group of the respondents were within 31 to 35 years' age group (39.82%), male (61.88%), living single (58.24%) and doctoral level students (39.8%). The preventive and supportive measures taken by students and/or provided by the respective institution or authorities were positively related to students' satisfaction and had an acceptable strength (β = 0.611, t = 9.679, p < 0.001). The trust gained in authorities also showed an acceptable strength (β = 0.381, t = 5.653, p < 0.001) with a positive direction. Again, the personnel awareness building related to both students' satisfaction (β = 0.295, t = 2.719, p < 0.001) and trust gain (β = 0.131, t = 1.986, p < 0.05) in authorities had a positive and acceptable intensity. Therefore, our study clearly demonstrates the great impact of preventive and supportive measures in the development of students' satisfaction (R2 = 0.507 indicating moderate relationship). The satisfied students possessed a strong influence which eventually helped in building sufficient trust on their institutions (R2 = 0.797 indicating above substantial relationship). Conclusions The worldwide student group is one of the most affected and vulnerable communities in this situation. So, there is a profound ground of research on how different states or authorities handle such situation. In this study, we have depicted the types and magnitude of care taken by Chinese government and educational institutions towards international students to relieve the panic of pandemic situation. Further research and such initiatives should be taken in to consideration for future emerging conditions.